Can Crowdsourcing Revolutionize Constitutional Amendments in Indonesia? A Comparative Study of International Experiences - Nggilu, Novendri; Ramdhan Kasim; Evi Noviawati; Andi Inar Sahabat; Tampubolon, Muhammad Hatta Roma (Universitas Negeri Semarang, 2025)
In the context of improving political systems and democracy, public participation in constitutional amendments has become increasingly important, but is often limited by existing mechanisms. In response to these limitations, Iceland and Estonia have implemented crowdsourcing models to engage the public in their constitutional amendment processes. This research aims to analyze the successes, challenges and potential of crowdsourcing in constitutional amendment, with a comparison between Iceland and Estonia, and its relevance for Indonesia. The findings show that while crowdsourcing has been successful in increasing public participation and transparency, significant challenges related to inequality in access to technology and the quality of public input remain. The novelty of this research lies in identifying the factors that influence the effectiveness of crowdsourcing in constitutional reform, as well as proposing an adaptation model for Indonesia that takes into account its social diversity and existing digital infrastructure. The research suggests that for the successful implementation of crowdsourcing in Indonesia's constitutional amendment, efforts are needed to create a more inclusive system and address existing digital inequalities.